Pengembangan Prototipe Alat Panen Sawit Bertenaga Listrik untuk Meningkatkan Produktivitas - Rizky Fauzi; Iswandi Iswandi; Tino Hermanto (CV. IRA PUBLISHING, 2025)
Using manual oil palm fruit harvesting tools requires a lot of energy and time, especially for trees with a height of more than 5 meters. This study aims to design and create an efficient, ergonomic, and environmentally friendly electric-based oil palm fruit harvesting tool. This system uses a DC electric motor controlled by a switch, with a sickle-shaped cutting blade driven by a transmission belt. The test results showed that the tool could cut oil palm bunches at 5-8 meters height with an average cutting time of 5-7 seconds per bunch. Power consumption was recorded at 150 Watts with a 24V 10Ah lithium battery power source.